PENDAMPINGAN DIGITALISASI INKUBASI BISNIS BERBASIS PLATFORM E-INKUBATOR UNTUK MENINGKATKAN DAYA SAING UMKM DI KELURAHAN MANYARAN SEMARANG - Sulastri, Sulastri; Murti, Hari; Andraini, Fitika; Radyanto, M Riza (Jurnal Abdi Insani, 2025)
UMKMs significantly contribute to local food security and the economy. However, many business actors still face challenges in accessing digital markets, managing business processes efficiently, and utilizing information technology. This digital gap weakens product competitiveness. To address this issue, this community engagement program aims to enhance the competitiveness of food UMKMs in Manyaran, Semarang through business incubation digitalization using the e-Inkubator platform. The method involved socialization, technical training on the platform, digital business process mentoring, and evaluation of the program’s impact on UMKM performance.The results show a significant improvement in digital capabilities, particularly in financial recordkeeping, online promotion, and inventory management. Around 85% of participants operated the platform independently, and 60% began marketing their products digitally. Product branding improved in terms of packaging design and promotional storytelling. Partners expressed high satisfaction with the program, as reflected in surveys and structured interviews.This activity effectively increased UMKM competitiveness through a structured and applicable digital business incubation approach.